2013
DOI: 10.1080/0092623x.2013.842195
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Sociodemographic Predictors of Sexual Problems in Portugal: A Population-Based Study With Women Aged 18 to 79 Years

Abstract: Studies on epidemiology of female sexual problems consistently indicate high prevalence rates worldwide, suggesting that this clinical presentation should be considered as a public health concern. However, there are no published studies on prevalence of sexual problems in Portugal. The present study investigated the prevalence, severity, and comorbidity of female sexual problems in a Portuguese community sample. In addition, the authors assessed the role of sociodemographic predictors of women's sexual difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 38 publications
3
35
1
2
Order By: Relevance
“…It might be that the context in which sex occurs for young adults sexual dysfunction can have a significant presence in younger adults. However, the percentage of participants reporting sexual difficulties in this study is lower than the percentage found previously in the general population and in other studies with adolescents and young adults (Farmer & Meston, 2007;Fisher & Boroditsky, 2000;Laumann et al, 1999;O´Sullivan et al, 2014;O´Sullivan & Majerovich, 2008;Peixoto & Nobre, 2015). This could be explained by the age difference between the general population and our sample.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…It might be that the context in which sex occurs for young adults sexual dysfunction can have a significant presence in younger adults. However, the percentage of participants reporting sexual difficulties in this study is lower than the percentage found previously in the general population and in other studies with adolescents and young adults (Farmer & Meston, 2007;Fisher & Boroditsky, 2000;Laumann et al, 1999;O´Sullivan et al, 2014;O´Sullivan & Majerovich, 2008;Peixoto & Nobre, 2015). This could be explained by the age difference between the general population and our sample.…”
Section: Discussioncontrasting
confidence: 55%
“…Most of the research that exists has focused on only one area of sexual functioning, such as sexual satisfaction or sexual desire, and has examined some aspects other than its prevalence (Carrobles, Gámez-Guadix, & Almendros, 2011;Santos-Iglesias, Calvillo, & Sierra, 2013). Other studies have focused on the study of sexual functioning but have used samples from the general population without examining adolescents and young adults in particular (Casas Aranda et al, 2007;Gomes & Nobre, 2014;SEXUAL FUNCTIONING IN YOUNG ADULTS Martín-Morales et al, 2001;Peixoto & Nobre, 2015;Sierra, Vallejo-Medina, Santos-Iglesias, & Lameiras Fernández, 2012;Teles et al, 2008).…”
mentioning
confidence: 99%
“…Most studies have found a significant positive relationship between age and lubrication difficulties (Laumann et al, 2008;Peixoto & Nobre, 2015). In the Global Survey of Sexual Attitudes and Behaviors, involving a sample of 9,000 women aged 40-80 years across 29 countries, age showed a curvilinear relationship with the likelihood of lubrication difficulties in most, but not all, countries (Laumann, Nicolosi, Glasser, Paik, et al, 2005).…”
Section: Aging Women's Sexual Problemsmentioning
confidence: 99%
“…Although age is a significant predictor of most female sexual problems (Lutfey, Link, Rosen, Wiegel, et al, 2009;Peixoto & Nobre, 2015), some studies have reported either a ACCEPTED MANUSCRIPT ACCEPTED MANUSCRIPT 8 negative association (Ishak, Low, & Othman, 2010;Sidi, Puteh, Abdulla, & Midin, 2007) or a Ushaped relationship (Hendrickx, Gijs & Enzlin, 2015) between age and pain-related problems.…”
Section: Aging Women's Sexual Problemsmentioning
confidence: 99%
See 1 more Smart Citation